2015
DOI: 10.1080/14786419.2015.1023727
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical study and absolute configuration of securinine oxidation products

Abstract: Time-dependant density functional theory-electronic circular dichroism spectra prediction was carried out to study the absolute configuration of phyllanthidine-type derivatives 5 and 6, derived from securinine (1) and its enantiomer virosecurinine (2), respectively. This method demonstrated to be very reliable in this alkaloid series. Thus, 5 and 6 shared the same stereochemistry as their parent precursors, confirming the retentive nature of the oxidation sequence. In addition, this study highlighted the key r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The NOE correlation between H-2′ and H-8′a in the NOESY spectrum of 2, as well as the significant similarities between the NMR data assigned to unit 2b and those of phyllanthidine suggested that 2b possessed consistent relative stereochemistry with phyllanthidine. 9 Besides, as depicted in the optimized molecular model of 2 (Figure 3), the NOE interactions between H 2 -5 and H-7/H-15 as well as between 15-OCH 3 and H-8b indicated that 15-OCH 3 and the C-7−C-8−C-9 carbon bridge were of the same orientation. To determine the absolute configuration of 2, the theoretical ECD spectra of four possible stereoisomers of 2 were predicted by TDDFT calculation.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…The NOE correlation between H-2′ and H-8′a in the NOESY spectrum of 2, as well as the significant similarities between the NMR data assigned to unit 2b and those of phyllanthidine suggested that 2b possessed consistent relative stereochemistry with phyllanthidine. 9 Besides, as depicted in the optimized molecular model of 2 (Figure 3), the NOE interactions between H 2 -5 and H-7/H-15 as well as between 15-OCH 3 and H-8b indicated that 15-OCH 3 and the C-7−C-8−C-9 carbon bridge were of the same orientation. To determine the absolute configuration of 2, the theoretical ECD spectra of four possible stereoisomers of 2 were predicted by TDDFT calculation.…”
mentioning
confidence: 81%
“…In addition, the HMBC correlations between H-2′ and C-6′/C-8′/C-13′, between H 2 -3′ and C-9′, between H-7′ and C-9′, between H 2 -8′ and C-13′/C-15′, between H-12′ and C-9′, as well as between H-14′ and C-7′/ C-9′/C-12′ established a phyllanthidine motif with a tetrahydro-1,2-oxazine ring (2b). 9 Furthermore, the HMBC correlations between H-7′/H-14′ and C-3 implied that two substructures 2a and 2b were also connected through the C-3−C-15′ bond. Hence, the gross structure of 2 was established and shown in Figure 3.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The resin petroleum extract was parboiled with agitation at 50˚C, then filtered until the crystals were separated out. Spectral techniques, including infra-red spectroscopy, ultraviolet-visible spectroscopy, mass spectrometry and nuclear magnetic resonance spectroscopy were used to identify the structure of the crystal, and X-ray crystallography, circular dichroism and Mosher chiral reagents were used to determine the absolute configuration of the product, as previously described (22,23). Finally, L-securinine was extracted and isolated, as described in the previous studies (Fig.…”
Section: Methodsmentioning
confidence: 99%